The level of socio-emotional competence of children treated for cancer - Faber, Karolina Agata; Jach-Salamon, Natalia (Psychoonkologia, 2015)
Introduction : The diagnosis of cancer is treated as a critical event in the life of the young patient and his entire family. The reason is that the sudden onset of it brings precipitation of daily functioning, bringing social and emotional problems. At the same time this situation increases the social and affective maturity and also strengthening bonds between family members and enhance their emotional empathy. The aim of the study was to assess the specificity of socio-emotional functioning of children treated for cancer. Material and methods : The study covered children treated for the cancer at the Department of Hematology, Oncology and Transplantation at the University Children’s Hospital in Lublin and their healthy peers. The study included 31 children who were treated of oncological and hematological and 31 healthy children. The selected tests of Intelligence and Development Scales (IDS): recognition of emotions, emotions adjustment, understanding social situations, social strategies were used for the measurement of socio-emotional competence of children. Results and conclusions : The results indicate that the children treated for cancer have a higher level of skills such as recognition, naming and differentiation of other people’s emotional states, as well as they can regulate their own emotions more effectively than healthy children. Nevertheless between the clinical and control group there was no difference in terms of social skills such as ability of proper understanding of social situations and use of social strategies. The authors emphasize the need for a broader research in the area of socio-emotional functioning of children treated for cancer and their families.